2018
DOI: 10.1080/15592294.2018.1514239
|View full text |Cite
|
Sign up to set email alerts
|

Histone variant macroH2A1 rewires carbohydrate and lipid metabolism of hepatocellular carcinoma cells towards cancer stem cells

Abstract: Hepatocellular carcinomas (HCCs) contain a sub-population of cancer stem cells (CSCs) that are responsible for tumor relapse, metastasis, and chemoresistance. We recently showed that loss of macroH2A1, a variant of the histone H2A and an epigenetic regulator of stem-cell function, in HCC leads to CSC-like features such as resistance to chemotherapeutic agents and growth of large and relatively undifferentiated tumors in xenograft models. These HCC cells silenced for macroH2A1 also exhibited stem-like metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 55 publications
4
51
0
Order By: Relevance
“…Previous studies have confirmed the reliability of our analysis results. For example, H2AFY has a significant correlation with lipid metabolism-related HCC (40), as it can also alter the lipid metabolism of HCC cells and allow tumour cells to be more adaptable to the changing microenvironment (23). Some evidence indicates that H2AFY is a new fusion gene companion for MECOM gene in patients with AML and may promote the development of AML, but the exact mechanism is unclear (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have confirmed the reliability of our analysis results. For example, H2AFY has a significant correlation with lipid metabolism-related HCC (40), as it can also alter the lipid metabolism of HCC cells and allow tumour cells to be more adaptable to the changing microenvironment (23). Some evidence indicates that H2AFY is a new fusion gene companion for MECOM gene in patients with AML and may promote the development of AML, but the exact mechanism is unclear (28).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of H2AFY mediates the phosphorylation level of the NF-ÎşBp65 (Ser536) pathway, which induces hepatoma cells to exhibit stemness (22). In HCC, as tumour cells exhibit stem cell-like properties, the loss of H2AFY can change the glucose metabolism and lipid metabolism in HCC cells, so that tumour cells can obtain energy and intermediate metabolites, which is beneficial for those cells to adapt to their changing microenvironment (23).…”
Section: Introductionmentioning
confidence: 99%
“…Along this line, LD accumulation could drive resistance to drugs, such as 5-fluorouracil and oxaliplatin [45], which are often used in combination with bevacizumab in metastatic colorectal cancer, and there are emerging mechanisms involving adypocytes and lipid metabolism in altering the response to cancer treatment [46]. Finally, other studies established that increased LD are a hallmark of ovarian CSCs as well as liver CSCs [31,32]. Interestingly, in our models we also found increased expression of CD117, a marker of ovarian CSCs [33] both in ex vivo cultures from bevacizumab-treated tumors and in IGROV-1 and SKOV3 cells grown under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that increased LD levels are a feature of CSCs in ovarian cancer [31] as well as liver cancer [32]. We, therefore, investigated whether bevacizumab treatment or incubation under hypoxic conditions could increase CD117 + cells, a sub-population endowed with CSCs features in ovarian cancer [33].…”
Section: Hypoxia Accounts For Increased Ld Accumulation and Expressiomentioning
confidence: 96%
“…For instance, an increase in acetyl-CoAdependent FA synthesis resulted in high intracellular lipid accumulation as well as a rewired carbohydrate metabolism leaning toward the pentose phosphate pathway, enabling the use of glycolytic intermediates for nucleotide synthesis in HCC cells. 34 Since they are highly metabolically flexible, CSCs induce β-oxidation to support their survival during glucose limiting conditions. For instance, in the hypoxic niche where the CSCs reside, an increased uptake of FA and LD accumulation is observed.…”
Section: Rewiring Of Lipid Metabolism In Cancer and Cscsmentioning
confidence: 99%